2018
DOI: 10.1080/01426397.2018.1446073
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of ecological and aesthetic quality by natural resource professionals and local people. A qualitative exploration in a mountainous landscape (La Rioja, Spain)

Abstract: This research analyses how aesthetic and ecological evaluations of the landscape studied overlap and interrelate in the attitudes of local people and natural resource professionals. The analytical framework adopted, built on Canter's Theory of Place, explores the people-place relationship by examining the interaction of three components: physical attributes, conceptions and activities. The findings show that the two groups differed in how they ascribed meaning to landscape and how they interpreted its ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…We do not refer, therefore, to social research for the identification of places or characteristics in which ecology is already beautiful from the point of view of general preferences. We refer to evaluations that highlight and deeply explore the bases of the different valuation in terms of esthetics and ecology that landscapes receive and link these perceptions to physical features of the landscape, as it is carried out, for example, in [57]. This focus of inquiry is conceptually different from the experiences abovementioned, whose outcomes, on the other hand and without a doubt, are not lacking in interest and utility.…”
Section: The Ecological Esthetic In Landscape Planning and Social Researchmentioning
confidence: 99%
“…We do not refer, therefore, to social research for the identification of places or characteristics in which ecology is already beautiful from the point of view of general preferences. We refer to evaluations that highlight and deeply explore the bases of the different valuation in terms of esthetics and ecology that landscapes receive and link these perceptions to physical features of the landscape, as it is carried out, for example, in [57]. This focus of inquiry is conceptually different from the experiences abovementioned, whose outcomes, on the other hand and without a doubt, are not lacking in interest and utility.…”
Section: The Ecological Esthetic In Landscape Planning and Social Researchmentioning
confidence: 99%
“…It was also indicated that aesthetic experiences could be evoked by different human perceptions of the environment [36]. Different emotional bonds and landscape experiences provide people with various perceived dimensions to understand a meaningful natural or built environment that incorporates values, ideas, and beliefs, conferring the physical space with a sense of place [5,39]. Specifically, some have suggested utilizing descriptive indicators to identify people's underlying perceptions [40].…”
Section: Perceived Dimensions In Landscape Aestheticsmentioning
confidence: 99%
“…People are affected by the aesthetics of nature, landscapes, and architecture [1][2][3][4]. Different landscape characteristics influence people's attitudes, and eventually translate to the landscape experience and aesthetic pleasure [5]. As a distinctive branch of the world's landscape family and excellent carriers of East Asian cultures, Chinese Classical Gardens (CCGs) encapsulate advantages of sustainability, ecological value, urban function, pleasure, and healthcare [6].…”
Section: Introductionmentioning
confidence: 99%
“…Different regional characteristics, customs, and religious beliefs have created different ethnic cultures and art forms, which have produced unique and diverse ethnic decorative element symbols [3][4]. Chinese traditional decorative patterns are cultural symbols of a nation, and also embody the cultural connotation of a nation [5][6]. Now that there is a large amount of material data on the Internet and arti cial intelligence technology has been rapidly developed, there is a new answer to the problem that the e ciency of traditional pattern design cannot meet the explosive growth of demand: the automatic generation of traditional patterns [7].…”
Section: Introductionmentioning
confidence: 99%